2019
DOI: 10.1162/ajhe_a_00106
|View full text |Cite
|
Sign up to set email alerts
|

Short-Run Effects of Parental Job Loss on Child Health

Abstract: Recent research suggests that parental job loss has negative effects on children's outcomes, including their academic achievement and long-run educational and labor market outcomes. In this paper we turn our attention to the effects of parental job loss on children's health. We combine health data from 16 waves of the Medical Expenditure Panel Survey, which allows us to use a fixed effects specification and still have a large sample of parental job displacements. We find that paternal job loss is detrimental t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
60
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 57 publications
13
60
1
Order By: Relevance
“…Notably, these findings contrast both with the literature on changes in adult health over the business cycle, which has generally shown that increased unemployment rates are associated with improvements in adult health, and with the literature on the relationship between unemployment rates and infant health, which has found that economic downturns are associated with reductions in infant mortality and the incidence of low birthweight. On the other hand, they are consistent with recent work looking at the direct effects of parental job displacement on child health: Schaller and Zerpa (2015) find that paternal job loss is associated with worse mental health among children and leads to increases in injuries among children in low-socioeconomic status families.…”
Section: ! !supporting
confidence: 89%
See 2 more Smart Citations
“…Notably, these findings contrast both with the literature on changes in adult health over the business cycle, which has generally shown that increased unemployment rates are associated with improvements in adult health, and with the literature on the relationship between unemployment rates and infant health, which has found that economic downturns are associated with reductions in infant mortality and the incidence of low birthweight. On the other hand, they are consistent with recent work looking at the direct effects of parental job displacement on child health: Schaller and Zerpa (2015) find that paternal job loss is associated with worse mental health among children and leads to increases in injuries among children in low-socioeconomic status families.…”
Section: ! !supporting
confidence: 89%
“…Our results echo those of recent studies that document differential impacts of individual maternal and paternal job loss on children's health and achievement (Schaller and Zerpa, 2015;Liu and Zhao, 2011;Kalil and Ziol-Guest, 2008). Our analyses differ from the previous research, however, because we focus on the impact of aggregate demand conditions, rather than individual job loss.…”
Section: B Mechanismssupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study regarding socio-demographic characteristics of parents, only employment status in fathers and age in both parents played important roles, a result consistent with previous data, suggesting the in uential effect of family socioeconomic status (SES) de ned as parental employment and family income on children's general health and risk of CVD development in adulthood [34][35][36]. Accordingly, previous ndings in Iran showed that moderate and low familial economic status could increase the incidence of HTN in school-aged children [18].…”
Section: Discussionsupporting
confidence: 88%
“…While the job loss literature suggests that there is a negative effect on health for job displacement (Sullivan and Von Wachter 2009), we show there is an intensive margin change in hours worked in addition to a change in employment. Further, it is not as clear that the negative health effects of job displacement hold for children: Schaller and Zerpa (2015) find that while paternal job loss is bad for child health, maternal job loss actually decreases incidences of infectious disease among children.…”
Section: Notesmentioning
confidence: 98%